2006
DOI: 10.1016/j.ccr.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles homolog 2 inactivates C/EBPα and causes acute myelogenous leukemia

Abstract: Tribbles homolog 2 (Trib2) was identified as a downregulated transcript in leukemic cells undergoing growth arrest. To investigate the effects of Trib2 in hematopoietic progenitors, mice were reconstituted with hematopoietic stem cells retrovirally expressing Trib2. Trib2-transduced bone marrow cells exhibited a growth advantage ex vivo and readily established factor-dependent cell lines. In vivo, Trib2-reconstituted mice uniformly developed fatal transplantable acute myelogenous leukemia (AML). In mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
260
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(275 citation statements)
references
References 51 publications
12
260
1
Order By: Relevance
“…In this study we identify the molecular mechanism involved in the dysregulation of C/EBPα expression via TRIB2 in AML. We and others (10,13,30) have previously demonstrated that TRIB2 overexpression induces AML and that it degrades C/EBPα p42. Here we provide novel insights on this process and show that the presence of C/EBPα p42 is required not only to initiate TRIB2 AML, but also for TRIB2 to cooperate with C/EBPα (p42 loss and increased p30) in driving AML disease.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In this study we identify the molecular mechanism involved in the dysregulation of C/EBPα expression via TRIB2 in AML. We and others (10,13,30) have previously demonstrated that TRIB2 overexpression induces AML and that it degrades C/EBPα p42. Here we provide novel insights on this process and show that the presence of C/EBPα p42 is required not only to initiate TRIB2 AML, but also for TRIB2 to cooperate with C/EBPα (p42 loss and increased p30) in driving AML disease.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, TRIB2 leads to the degradation of C/EBPα p42 via E3 ligase COP1 binding whilst sparing p30 from degradation, resulting in disturbed granulopoiesis. This modulation of C/EBPα was found to be critical for the induction of AML in vivo (10,13). E2F1 cooperates with C/EBPα p30 to activate the Trib2 promoter in preleukaemic cells resulting in elevated TRIB2 expression.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A mechanism for this was defined: Trbl binds to and promotes proteosome degradation of the fly C/EBP (CAAT enhancer binding protein) homolog encoded by the gene slow border cells (slbo), a key promoter of border cell migration. Subsequent work indicates that this interaction is highly conserved with Trib1 and Trib 2 in several mammalian tissues: (1) in acute myelogenous leukemia (AML) tumors, Trib1 accelerates degradation of C/EBPa; (2) upregulation of C/EBPb occurs in Trib1 knockout mice (Yamamoto et al, 2007;Keeshan et al, 2008); (3) overexpression of Trib2 reduces C/EBPa levels in a proteasome-dependent manner, resulting in myeloid differentiation (Keeshan et al, 2006); and (3) Trib2 (but not Trib3) increases degradation of C/EBPb, effectively suppressing differentiation of 3T3-L1 preadipocytes (Naiki et al, 2007).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Trib2 is up-regulated in acute myelogenous leukemia tumors (AML) and misexpression leads to growth advantages and transplantable tumors (Keeshan et al, 2006). While Trib2 directs turnover of C/EBPa in these tumor cells, C/EBPa mutants do not result in AML, making it likely that Trib2 has more targets (Keeshan et al, 2006).…”
Section: Tribs As Oncogenesmentioning
confidence: 99%